2020
DOI: 10.1515/secm-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and compressive behavior of lamellar Al2O3p/Al composite prepared by freeze-drying and mechanical-pressure infiltration method

Abstract: Infiltrated molten Al matrix by mechanical-pressure infiltration method into the ceramic scaffold prepared by freeze-drying technology could prepare dense lamellar Al matrix composites without damage of the biomimetic microstructure of the scaffold. However, the investigation of lamellar Al matrix composites prepared by freeze-drying and mechanical-pressure infiltration method has not been fully understood yet. In the present work, the Al2O3 scaffold with pearl layer structure was prepared by freezing-dry meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Though the pressureless infiltration method [22,23] is economical and has the benefits of easy industrialization, pressure infiltration [24,25] is preferred for the manufacture of C4 due to its lower infiltration time, performance, and efficiency. A recent study by Zhang et al [26] reported that mechanical-pressure infiltration method was effective for producing Al 2 O 3 /Al based materials for scaffoldings. The study also reported that the pressure infiltration technique enhanced the interfacial bonding between Al 2 O 3 layers and the infiltrant Al alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Though the pressureless infiltration method [22,23] is economical and has the benefits of easy industrialization, pressure infiltration [24,25] is preferred for the manufacture of C4 due to its lower infiltration time, performance, and efficiency. A recent study by Zhang et al [26] reported that mechanical-pressure infiltration method was effective for producing Al 2 O 3 /Al based materials for scaffoldings. The study also reported that the pressure infiltration technique enhanced the interfacial bonding between Al 2 O 3 layers and the infiltrant Al alloy.…”
Section: Introductionmentioning
confidence: 99%